Struktur Komunitas Lamun di Perairan Distrik Salawati Utara Kabupaten Raja Ampat - Franklyn Hoek; Abudarda Razak; Hamid Hamid; Muhfizar Muhfizar; Amir M Suruwaky; M Ali Ulat; Mustasim Mustasim; Arhandy Arfah (Politeknik Kelautan dan Perikanan Sorong, Indonesia, 2018)
This study aims to analyze seagrass community structure in North Salawati District, Raja Ampat. The scope of research is limited to identification of seagrass biodiversity, analyzing the overrune level of seagrass type covering the area, analyzing the densities types of seagrass important value index frequencies, water parameters and seagrass area. Research method was purposive sampling by using transects with dimensions of 1 x 1 meter with a total of seven stations along 100 meters of seagrass area. The acquired data was analyzed by using analysis of closure type, density type, frequency type, and important value index. Results of biodiversity identification showed that there are two families of seagrass, Eight species of seagrass covering the area. The overrune of seagrass covering the area in both stations is very high. The area of coverage in the both areas is above 60% (> 60%), which classified as